Use of Idarucizumab for dabigatran reversal: Emergency department experience in two cases with subdural haematoma. (February 2018) - Edwards, Gail; Roman, Cristina; Jithoo, Rondhir; Mitra, Biswadev
Abstract: Introduction: Idarucizumab is the first effective humanized monoclonal antibody fragment developed specifically as a reversal agent for dabigatran, a Direct Oral Anticoagulant. Despite recent trials demonstrating reversal of clinically relevant bleeding, there is a paucity of data on use outside the trial setting. This manuscript describes the use of Idarucizumab to reverse dabigatran in two patients presenting to the emergency department of a major tertiary hospital with acute traumatic subdural haematomas (SDH). Methods: Patients were identified through retrospective review of medication dispensing systems and electronic medical records. Results: Two cases of Idarucizumab use were identified. Case 1 was of a 63-year-old male who presented following a motorcycle crash. Case 2 was of a 77-year-old male who presented with a 3-week history of ataxia and recurrent falls. Both patients were taking dabigatran for atrial fibrillation (AF). CT Brain revealed acute SDH with clinical indications for urgent surgical evacuation. Serum dabigatran levels were obtained on arrival in the emergency department with levels of 155 ng/ml and 110 ng/ml (reference range 117–275 ng/ml). Idarucizumab for dabigatran reversal was commenced; Case 1 received 5 g Idarucizumab as an intravenous bolus dose, while Case 2 received 5 g Idarucizumab as two 2.5 g intravenous infusions. Serum dabigatran levels for Cases 1 and 2 were 0 ng/ml at 75 min and 340 min post Idarucizumab administration respectively. Both patients proceeded to craniotomy with evacuation of the SDH. There was no extension of the SDH in either case. Anticoagulation was withheld until outpatient clinic review, and both patients transferred for rehabilitation prior to discharge home. Conclusion: Idarucizumab was clinically effective for reversing dabigatran, resulting in undetectable serum levels, and should be considered in patients presenting to hospital with clinically significant bleeding associated with dabigatran therapy.